Subsurface mapping and geochemical investigation of a marble deposit around Igarra, Southwestern Nigeria - Oluwajana, Oladotun; Ogunyele, Abimbola; Egunjobi, Joseph; Ajayi, Aiyedotun (International Journal of Advanced Geosciences, 2018)
Subsurface mapping of a marble deposit around Igarra and geochemical analysis of seven marble samples collected at different depths in four drill holes were carried out with the aim of determining the chemical compositions and economic viabilities of the deposit. Subsurface mapping and lithologic description revealed that snow-white and grey to dark grey marble layers occur in the four drill holes. Results of the geochemical analysis show that the CaO and MgO contents of the snow-white marble samples retrieved from depths between 10 m and 20 m (43.90-48.90 wt. % and 0.19-2.35 wt. % respectively) reflected calcitic to fairly dolomitic nature of the marble samples. This is confirmed by the high CaCO3 (91.65-95.75 wt. %) content of the samples. Grey to dark grey marble samples taken from depths between 30 m and 48 m have moderately high CaO contents (44.00-52.60 wt. %) and significantly high MgO contents (3.50-8.70 wt. %) which makes them highly dolomitic and impure. The pure, calcitic to fairly dolomitic marble is considered suitable as raw material for Portland cement production, flux in steel making and for paper production while the impure, dolomitic marble is suitable for making dimension stones and structural wares for landscaping purpose.